Trafficking in the Erotic Labor Market: A National Survey. Issue 2 (3rd April 2021) - Bishop-Royse, Jessica; Bastian, Danielle; Heart, Crysta; Scott, Greg
ABSTRACT: Methodological obstacles limit most estimates of trafficking among sex workers in the United States. The diversity of activities and interactions in the erotic labor market (ELM) demand an empirical approach more nuanced than what has been utilized in much of the previous research on this topic. We address this area of the literature with results from a first of its kind quantitative study on trafficking in the ELM. This community-based participatory research utilized a web survey to collect anonymous responses from over 1, 000 individuals engaged in the ELM (workers, managers, support staff, and clients) on their experiences with trafficking. In addition to documenting its presence in all sectors of the ELM, we find great heterogeneity among participants' experience with and exposure to trafficking, which has previously been underreported. We provide evidence that those engaged in all sectors of the ELM may be important in the identification of trafficked individuals. Policies that criminalize commercial sex discourage reporting trafficked individuals and should be reconsidered.